Фінансово-економічні показники як індикатори специфічних явищ в умовах невизначеності - Шестопалов, О. Г. (ХНУРЕ, 2017)
The given work is devoted to the problem of decision-making under conditions of uncertainty. The article considers the difficulties of forecasting and suggests a new approach to the analysis of enterprises in conditions of uncertainty. An example of such consideration is the economic phenomenon (Raiding).
Keywords: економічне моделювання; управління проектами; фінансово-економічні показники